Together with a 1 1 F 2 and a 2 2 F 3 we obtain a n F n 1 2 Again consider the

Together with a 1 1 f 2 and a 2 2 f 3 we obtain a n f

This preview shows page 95 - 100 out of 120 pages.

Together witha1=1=F2anda2=2=F3, we obtainan=Fn+1.2.Again consider the set of different possible strings. This set may be divided into two nonoverlappingsubsets: those strings for which the one andnare not interchanged, and those strings for which theyare interchanged. For the former, the number of different strings is given byan=Fn+1. For the latter,the number of different strings is given byan-2=Fn-1. We therefore havebn=Fn+1+Fn-1.From (1.3), the relation satisfied bybnis the same as that satisfied by thenth Lucas number, so thatbn=Ln.
Background image
90APPENDIX C. PROBLEM AND PRACTICE QUIZ SOLUTIONSSolutions to thePractice quiz: The Fibonacci numbers1.c. See alsoLecture 1. The relevant table for the rabbit pair population ismonthJFMAMJJASONDJjuvenile101123581321345589adult01123581321345589144total1123581321345589144233The number of adult rabbit pairs in the fifth month is 3.2.c. See alsoLecture 1, Problem 1. The Fibonacci numbers can be extended to negative indices usingthe recursion relation. The result isF-n= (-1)n+1Fn. Whenn=5, we haveF-5=F5=5.3.c.See alsoLecture 1, Problem 4.If we line up the Fibonacci numbers and the Lucas numbersproperly, we haveFibonacci011235813Lucas13471118and it can be observed (without proof) thatLn=Fn-1+Fn+1. We can also use the Fibonacci recursionrelation to lower the index ofFn+1(andFn). We haveFn+1=Fn+Fn-1= (Fn-1+Fn-2) +Fn-1=2Fn-1+Fn-2.Therefore,Ln=Fn-1+Fn+1=3Fn-1+Fn-2.Both A and B are true.
Background image
91Solutions to theProblems for Lecture 31.(a)Φ-1=5+12-1=5-12=φ,(b)1Φ=21+5×1-51-5=21-5-4=5-12=φ.(c)Φ2=5+12!2=5+25+14=5+32=Φ+1.(d)φ2=5-12!2=5-25+14=-5+32=-φ+1.2.We multiply1Φ=Φ-1byΦand rearrange to obtainΦ2=Φ+1.
Background image
92APPENDIX C. PROBLEM AND PRACTICE QUIZ SOLUTIONSMultiplying both sides byΦn-1yields the desired result:Φn+1=Φn+Φn-1.3.We substituteφ=1/Φinto1Φ=Φ-1to obtainφ=1φ-1.Multiplying both sides byφnand rearranging terms yields the desired result:φn-1=φn+φn+1.
Background image
93Solutions to theProblems for Lecture 41.WriteFk+nFk=Fk+nFk+n-1×Fk+n-1Fk+n-2× · · · ×Fk+1Fk.Then taking limk, and usinglimjFjFj-1=Φ,one obtains directlylimkFk+nFk=Φn.2.We prove (4.2) by mathematical induction.Base case:Forn=1, the relation (4.2) becomesΦ=Φ, which is true.Induction step:Suppose that (4.2) is true for positive integern=k. Then we haveΦk+1=ΦΦk=Φ(FkΦ+Fk-1)(from induction hypothesis)=FkΦ2+Fk-1Φ=Fk(Φ+1) +Fk-1Φ(fromΦ2=Φ+1)= (Fk+Fk-1)Φ+Fk=Fk+1Φ+Fk(from recursion relation)so that (4.2) is true forn=k+1. By the principle of induction, (4.2) is therefore true for all positiveintegers.
Background image
Image of page 100

You've reached the end of your free preview.

Want to read all 120 pages?

  • Fall '16
  • Jamie Watson
  • Fibonacci number, Golden ratio

  • Left Quote Icon

    Student Picture

  • Left Quote Icon

    Student Picture

  • Left Quote Icon

    Student Picture